Penerapan Activity Based Costing Dalam Meningkatkan Akurasi Biaya Dan Harga Produk Di Caffe Betokaw Coffe: The Application of Activity-Based Costing in Improving Cost Accuracy and Product Pricing at Caffe Betokaw Coffee - Dede Fenti Suharti; Endah Tri Hartini; Lisma Aulia Silva; Sintia Nur Wahyu; Tri Lestari (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to analyze the implementation of the Activity-Based Costing (ABC) method and the accuracy of cost information in determining the cost of goods manufactured at Caffe Betokaw Coffe. The ABC method is an accounting approach that allocates costs more precisely based on specific activities in the production process, differing from traditional methods that may be less consistent with the production flow. Caffe Betokaw Coffe, a coffee shop located in the Ciledug area of Tangerang, previously used the Break Event Point (BEP) method to determine its product selling prices. However, the company's calculation of the cost of goods manufactured was considered less accurate. This research utilizes a qualitative method with a descriptive approach. Data was collected through interviews regarding the calculation of the cost of goods manufactured at Caffe Betokaw Coffe, and then analyzed using the Activity-Based Costing (ABC) method. Two product samples, Arenga Sugar Milk Coffee and Toasted Bread, were selected for this study. This study reveals that the Activity Based Costing (ABC) method produces a more accurate calculation of production costs and is significantly different from the company's method, with the finding of overcost in the company's calculations. Therefore, Betokaw Coffee is highly recommended to implement the ABC method in order to obtain more accurate cost information and help determine the right product selling price.